Defining Structure‐Function Relationships of Amphiphilic Excipients Enables Rational Design of Ultra‐Stable Biopharmaceuticals - Alexander N. Prossnitz; Leslee T. Nguyen; Noah Eckman; Suraj Borkar; Samantha Tetef; Anton A. A. Autzen; Gerald G. Fuller; Eric A. Appel (Advanced Science)
Abstract Biopharmaceuticals are the fastest‐growing class of drugs in the healthcare industry, but their global reach is severely limited by their propensity for rapid aggregation. Currently, surfactant excipients such as polysorbates and poloxamers are used to prevent protein aggregation, which significantly extends shelf‐life. Unfortunately, these excipients are themselves unstable, oxidizing rapidly into 100s of distinct compounds, some of which cause severe adverse events in patients. Here, the highly stable, well‐defined, and modular nature of amphiphilic polyacrylamide‐derived excipients is leveraged to isolate the key mechanisms responsible for excipient‐mediated protein stabilization. With a library of compositionally identical but structurally distinct amphiphilic excipients, a new property is quantified, compositional dispersity, that is key to excipient performance and utilized this property to rationally design new ultra‐stable surfactant excipients that increase the stability of a notoriously unstable biopharmaceutical, monomeric insulin, by an order of magnitude. This comprehensive and generalizable understanding of excipient structure‐function relationships represents a paradigm shift for the formulation of biopharmaceuticals, moving away from trial‐and‐error screening approaches toward rational design.